Does Age Affect the Short- and Long-Term Outcomes of Coronary Bypass Grafting? - Anand, Pavan Ashwini; Keshavamurthy, Suresh; Shelley, Ellis M.; Saha, Sibu (International Journal of Angiology, 2021)
The etiology of coronary artery disease (CAD) is multifactorial, stemming from both modifiable and nonmodifiable risk factors such as age. Several studies have reported the effects of age on various outcomes of coronary artery bypass grafting (CABG). This article reviews age-related outcomes of CABG and offers direction for further studies in the field to create comprehensive, evidence-based guidelines for the treatment of CAD. Ninety-two primary sources were analyzed for relevance to the subject matter, of which 17 were selected for further analysis: 14 retrospective cohort studies, 2 randomized clinical trials, and 1 meta-analysis. Our review revealed four broad age ranges into which patients can be grouped: those with CAD (1) below the age of 40 years, (2) between the ages of 40 and 60 years, (3) between the ages of 60 and 80 years, and (4) at or above 80 years. Patients below the age of 40 years fare best overall with total arterial revascularization (TAR). Patients between the ages of 40 and 60 years also fare well with the use of multiarterial grafts (MAGs) whereas either MAGs or single-arterial grafts may be of significant benefit to patients at or above the age of 60 years, with younger and diabetic patients benefitting the most. Arterial grafting is superior to vein grafting until the age of 80 years, at which point there is promising evidence supporting the continued use of the saphenous vein as the favored graft substrate. Age is a factor affecting the outcomes of CABG but should not serve as a barrier to offering patients CABG at any age from either a cost or a health perspective. Operative intervention starts to show significant mortality consequences at the age of 80 years, but the increased risk is countered by maintenance or improvement to patients' quality of life.
Keywords: coronary artery bypass grafting (CABG); age-related outcomes; mortality; total arterial revascularization (TAR)